Investigation of Water-Stability Behaviors in Coastal Mud Multiply Modified by Cement and Coarse-Particle Spoil - Zipeng Qin; Yan Tian; Xianding Guo; Jiongzhang Chen; Huang Huang; Zongkai Ye; Dongxue Wang; Erjin Xu; Hanwei Huang; Xinxin Chen (Journal of Marine Science and Engineering, 2025)
This study investigates the water-stability performance and stabilization mechanism of a hybrid-modified dredged muck sampled from the protection channel of the southern seawall, Cangnan County, China, and explores the feasibility of reusing the modified soil as backfill or non-structural fill behind the dike body. The muck was amended with two industrial by-products: (i) coarse-grained spoil excavated from an adjacent power-plant project, serving as a particle-size modifier, and (ii) ordinary Portland cement, acting as the chemical stabilizer. Unconfined compressive strength (UCS) tests were conducted on specimens cured for 7 d and 28 d under both saturated and unsaturated conditions, complemented by scanning electron microscopy (SEM) to elucidate microstructural evolution. An optimal mix proportion that satisfies the prescribed water-stability criterion while maintaining cost-effectiveness was thereby identified. Experimental results demonstrate that cement content, coarse-spoil fraction and curing age govern the water-stability behavior, with cement dosage exerting the most pronounced influence. A 28 d cured blend containing only 5% cement yielded a low water-stability coefficient (31.8%) and negligible post-immersion strength. Conversely, a ternary mixture comprising 40% muck, 60% coarse spoil and 15% cement achieved the highest water stability, recording UCS values of 1582 kPa (saturated) and 2025 kPa (unsaturated), corresponding to 78.1%. These findings provide a theoretical basis and practical guidance for the valorization of waste soils in coastal engineering and for the design/construction of seawalls. These findings not only provide a theoretical basis and practical guidance for the valorization of waste soils in coastal engineering and for the design/construction of seawalls, but also substantially expand the available material source, drive down construction costs, and markedly mitigate the environmental impacts associated with the off-site disposal of excavated waste.

Chronic heat stress is capable of reducing the growth performance, causing damage to the liver structure, and altering the liver glucose metabolism and lipid metabolism in largemouth bass (Micropterus salmoides L.) - Hanwei Yan; Jinxing Du; Shengjie Li; Caixia Lei; Tao Zhu; Linqiang Han; Hongmei Song (Fish Physiology and Biochemistry, 2025)

Genome-wide identification of the Carya illinoinensis bZIP transcription factor and the potential function of S1-bZIPs in abiotic stresses - Nianqin Jiang; Linna Wang; Yangang Lan; Hongxia Liu; Xiaoyue Zhang; Wei He; Min Wu; Hanwei Yan; Yan Xiang (Tree Genetics & Genomes, 2023)

Anthropogenic activity and millennial climate variability affect Holocene mercury deposition of an alpine wetland near the largest mercury mine in China - Haijun Peng; Yimeng Rong; Di Chen; Ruiyang Sun; Jie Huang; Hanwei Ding; Carolina Olid; Haiyu Yan (Chemosphere, 2023)

Genetic variation analysis and comprehensive evaluation of wood property traits of 20-year-old Chinese fir clone - Demiao Chu; Tao Yao; Liang Zhou; Hanwei Yan; Min Yu; Yamei Liu; Yunfei You; Mohsen Bahmani; Changqing Lu; Zhenhao Ding; Shengquan Liu (European Journal of Forest Research, 2022)

A Moso bamboo gene VQ28 confers salt tolerance to transgenic Arabidopsis plants - Xinran Cheng; Yujiao Wang; Rui Xiong; Yameng Gao; Hanwei Yan; Yan Xiang (Planta, 2020)

Free and hidden fumonisins in raw maize and maize-based products from China - Ling Hu; Hanwei Liu; Jian Yang; Chunfang Wang; Yongjian Wang; Yan Yang; Xianfeng Chen (Food Additives & Contaminants Part B-Surveillance, 2019)

The effects of CXCL10 polymorphisms on COPD susceptibility - Yan Wang; Qipeng Zhou; Lian Dong; Mingmei Xiong; Hua Jiang; Meihua Guo; Li Zhao; Liang Yuan; Ziying Li; Hanwei Liu; Jian Wang; Nanshan Zhong; et al. (Molecular Genetics and Genomics, 2018)

Genome-wide identification, classification, and expression of phytocyanins in Populus trichocarpa - Shuangshuang Luo; Wenfang Hu; Yue Wang; Bin Liu; Hanwei Yan; Yan Xiang (Planta, 2018)

Genome-wide analysis of VQ motif-containing proteins in Moso bamboo (Phyllostachys edulis) - Yujiao Wang; Huanlong Liu; Dongyue Zhu; Yameng Gao; Hanwei Yan; Yan Xiang (Planta, 2017)

Genome-Wide Identification and Expression Analysis of the HD-Zip Gene Family in Moso Bamboo (Phyllostachys edulis) - Danmei Chen; Zhu Chen; Min Wu; Yue Wang; Yujiao Wang; Hanwei Yan; Yan Xiang (Journal of Plant Growth Regulation, 2017)

Genome-wide analysis of poplar VQ gene family and expression profiling under PEG, NaCl, and SA treatments - Wenyuan Chu; Bin Liu; Yujiao Wang; Feng Pan; Zhu Chen; Hanwei Yan; Yan Xiang (Tree Genetics & Genomes, 2016)

Genome Duplication and Evolution of Heat Shock Transcription Factor (HSF) Gene Family in Four Model Angiosperms - Yuxin Zhu; Hanwei Yan; Yiyi Wang; Lin Feng; Zhu Chen; Yan Xiang (Journal of Plant Growth Regulation, 2016)

Genome-wide survey and expression analysis of the amino acid transporter gene family in poplar - Min Wu; Shengnan Wu; Zhu Chen; Qing Dong; Hanwei Yan; Yan Xiang (Tree Genetics & Genomes, 2015)

Genome-wide analysis of HD-Zip genes in grape (Vitis vinifera) - Haiyang Jiang; Jing Jin; Huan Liu; Qing Dong; Hanwei Yan; Defang Gan; Wei Zhang; Suwen Zhu (Tree Genetics & Genomes, 2015)

Genome-wide identification and characterization of maize expansin genes expressed in endosperm - Wei Zhang; Hanwei Yan; Weijun Chen; Jinyang Liu; Cuiping Jiang; Haiyang Jiang; Suwen Zhu; Beijiu Cheng (Molecular Genetics and Genomics, 2014)